Cannabinoid CB1 and CB2 Receptor-Mediated Arrestin Translocation: Species, Subtype, and Agonist-Dependence - Ibsen, Mikkel Søes; Finlay, David B.; Patel, Monica; Javitch, Jonathan A.; Glass, Michelle; Grimsey, Natasha Lillia (Frontiers in Pharmacology, 2019)
Arrestin translocation and signalling have come to the fore of the G protein-coupled receptor molecular pharmacology field. Some receptor-arrestin interactions are relatively well understood and considered responsible for specific therapeutic or adverse outcomes. Coupling of arrestins with cannabinoid receptors 1 (CB1) and 2 (CB2) has been reported, though the majority of studies have not systematically characterised the differential ligand dependence of this activity. In addition, many prior studies have utilised bovine (rather than human) arrestins, and the most widely applied assays require reporter-tagged receptors, which prevent meaningful comparison between receptor types. We have employed a bioluminescence resonance energy transfer (BRET) method that does not require the use of tagged receptors and thereby allows comparisons of arrestin translocation between receptor types, as well as with cells lacking the receptor of interest – an important control. The ability of a selection of cannabinoid agonists to stimulate cell surface translocation of human and bovine β-arrestin-1 and -2 was assessed. We find that some CB1 ligands induce moderate β-arrestin-2 translocation in comparison with vasopressin V2 receptor (a robust arrestin recruiter), however CB1 coupling with β-arrestin-1 and CB2 with either arrestin elicited low relative efficacies. A range of efficacies between ligands was evident for both receptors and arrestins. Endocannabinoid 2-arachidonoylglycerol (2-AG) stood out as a high efficacy ligand for translocation of β-arrestin-2 via CB1. ∆9-tetrahydrocannabinol (THC) was generally unable to elicit translocation of either arrestin subtype via CB1 or CB2, however control experiments revealed translocation in cells not expressing CB1/CB2, which may assist in explaining some discrepancy with the literature. Overexpression of GRK2 had modest influence on CB1/CB2-induced arrestin translocation. Results with bovine and human arrestins were largely analogous, but a few instances of inconsistent rank order potencies/efficacies between bovine and human arrestins raise the possibility that subtle differences in receptor conformation stabilised by these ligands manifest in disparate affinities for the two arrestin species, with important potential consequences for interpretation in ligand bias studies. As well as contributing important information regarding CB1/CB2 ligand-dependent arrestin coupling, our study raises a number of points for consideration in the design and interpretation of arrestin recruitment assays.